Non-ST-Elevation Myocardial Infarction in a Case of Von Willebrand Disease: a Case Report - Abdul, Anees (Adv J Emerg Med, 2018)
INTRODUCTION: Studies have shown that patients with Von Willebrand disease (VWD) have decreased prevalence of thrombotic events like myocardial infarction (MI). Here we describe a case of VWD with acute non-ST-elevation MI with ongoing bleeding manifestations. CASE PRESENTATION: A 37-year-old female patient presented to the emergency department with a complaint of central chest pain since 7 days. She also had a history of hemoptysis since 8 days. Electrocardiogram (ECG) revealed ST-segment depression in leads I, aVL, II, III, aVF, and V(4)–V(6) compatible with diagnosis of Non-ST-Elevation Myocardial Infarction (Non STEMI). She was started on nitroglycerine infusion, angiotensin II receptor blockers, and calcium channel blockers along with trimetazidine. Her chest pain and ECG changes settled after 2 days, and she was discharged in a stable condition. CONCLUSION: There are limited studies available regarding the management of acute MI in VWD patients with acute bleeding manifestations. Further studies have to be carried out to determine successful ways of managing thrombotic events like MI in this subset of patients.